Excited state properties of aryl carotenoids - Fuciman, Marcel; Chábera, Pavel; Zupcanová, Anita; Hríbek, Petr; Arellano, Juan B; Vácha, Frantisek; Psencík, Jakub; Polívka, Tomás (Physical chemistry chemical physics, 2010)
Excited-state properties of aryl carotenoids, important components of light harvesting antennae of green sulfur bacteria, have been studied by femtosecond transient absorption spectroscopy. To explore effects of the conjugated aryl group, we have studied a series of aryl carotenoids with conjugated phi-ring, chlorobactene, beta-isorenieratene and isorenieratene, and compared them with their non-aryl counterparts gamma-carotene and beta-carotene, which contain beta-ring. Changing beta-ring to phi-ring did not reveal any changes in absorption spectra, indicating negligible effect of the phi-ring on the effective conjugation length. This observation is further supported by the carotenoid S(1) lifetimes. In n-hexane, the S(1) lifetime of chlorobactene having one phi-ring is 6.7 ps, while the S(1) lifetime of the beta-ring analog, gamma-carotene is 5.4 ps. The same effect is observed for the series beta-carotene (two beta-rings), beta-isorenieratene (one beta- and one phi-ring) and isorenieratene (two phi-rings) whose S(1) lifetimes in n-hexane are 8.2, 10.3 and 12.7 ps, respectively. The systematically longer lifetimes of aryl carotenoids show that the additional conjugated C=C bonds at the phi-ring do not contribute to the conjugation length. The S(1) lifetimes of aryl carotenoids were slightly shortened in benzene, indicating pi-pi stacking interaction between the phi-ring and benzene.
Keywords: časové faktory; spektrofotometrie; Time Factors; Spectrophotometry; Chlorobi; Quantum Theory; kvantová teorie; beta-karoten; beta Carotene; Carotenoids; karotenoidy